2019
DOI: 10.1007/s40368-019-00504-x
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic efficacy of cone beam computed tomography in paediatric dentistry: a systematic review

Abstract: Purpose To determine in which clinical situations it is indicated or contra-indicated to prescribe cone beam computed tomography (CBCT) for paediatric patients. Methods Systematic review of in vivo paediatric research studies of diagnostic efficacy using CBCT, with supplementary searches for guideline documents on CBCT and for systematic reviews permitting inclusion of ex vivo and adult studies. Results After screening, 190 publications were included, mostly case studies. No systematic reviews were found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
(84 reference statements)
0
22
0
6
Order By: Relevance
“…However, due to difficulties with access, it may not always be possible to assess this parameter. Also, diagnostic accuracy is subjective in nature and can vary from one person to another (Horner et al, 2020). Lastly, CBCT scans were performed with voxel size of 90 microns.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to difficulties with access, it may not always be possible to assess this parameter. Also, diagnostic accuracy is subjective in nature and can vary from one person to another (Horner et al, 2020). Lastly, CBCT scans were performed with voxel size of 90 microns.…”
Section: Discussionmentioning
confidence: 99%
“…In a review evaluating the use of CBCT in the field of endodontics, it was stated that CBCT would be useful in preoperative procedures such as the evaluation of periapical pathologies, root fractures, and resorption and/or postoperative evaluations. In their systematic review, Horner et al 7 stated that the use of CBCT for caries detection is not indicated in the paediatric population, but it may be indicated in cases such as acute infections and root resorption and fractures, where conventional radiographs are inadequate. According to the researchers, CBCT is indicated for the evaluation of developmental deformities and large bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT involves a higher radiation dose than panoramic and intra-oral imaging but a lower dose compared to conventional tomography. 4,7 When evaluating an individual's radiation risk, the effective doses recommended by ICRP (International Commission on Radiological Protection) should be kept in mind. Using anthropometric phantom models, Theodorakou et al 3 determined that the lowest effective dose was achieved by selecting the smallest fields of view (FOV) and using small patient size settings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DHCPs should delay entry into the operatory until a sufficient time has elapsed for enough air changes to remove potentially infectious particles. 13 , 52 Air changes per hour’ is the ratio of the volume of air flowing through a space in a certain period of time (the airflow rate) to the volume of that space (the room volume). Though ideally this should be 12 air changes per hour, particularly in new construction or recent renovations, a minimum of 6 is acceptable.…”
Section: Post-imaging Room Cleaningmentioning
confidence: 99%
“…Therefore, DHCPs should delay entry into the operatory until a sufficient time has elapsed for enough air changes to remove potentially infectious particles. 13 , 52 …”
Section: Post-imaging Room Cleaningmentioning
confidence: 99%